Pengaruh Locus of Control, Emotional Quotient, Skeptisme dan Kompleksitas Tugas terhadap Kualitas Audit di KAP Kota Palembang - Felix Andrian; Sri Rahayu; Netty Herawaty; Rahayu Rahayu (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
This research was conducted with the aim of examining the factors that are thought to affect audit quality in Palembang City. The population in this study were auditors who worked at KAP in Palembang City. This research was conducted with a total population of 10 KAP offices in Palembang City which had 64 auditors as respondents in this study. The results of the study concluded that locus of control, emotional intelligence, skepticism, and task complexity have an effect on audit quality.